Disinformation as a national complex phenomenon: societal and informatics approaches - Angela GLOBA; Ala GASNAS; Dumitru ANDONI; Nicu ENI (Acta et Commentationes, Sciences of Education, 2025)
The advancement of information and media literacy competencies has become increasingly significant, driven by the current challenges that the Republic of Moldova faces in the area of disinformation. Manipulation and propaganda through the dissemination of false news represent some of the primary factors necessitating concerted efforts to foster critical thinking and enhance societal resilience to disinformation. This article examines the normative framework of the Republic of Moldova regarding access to accurate information and outlines initiatives undertaken by state institutions. Furthermore, it provides a comparative analysis of specialized information systems developed for the detection of fake news.